Late Wisconsin white spruce ( Picea glauca (Moench) Voss) at Brampton, Ontario - Terasmae, J.; Matthews, H. L. (Canadian Journal of Earth Sciences, 1980)
Study of late Wisconsin deposits in a small bog on the crest of Brampton esker (mantled by the Halton Till), about 30 km west of Toronto, Ontario, yielded a radiocarbon date of 12 320 ± 360 years BP (BGS-551) for a sample of white spruce cones that contained fully-developed seeds. This date on cones (in gyttja) provides an estimate of minimum age for the lower boundary of the spruce pollen zone in southern Ontario. Silty clay beneath the gyttja yielded leaves of Dryas integrifolia and pollen assemblages (a herb pollen zone) that indicate presence of a dwarf-shrub tundra (essentially treeless) type of vegetation.This study supports the Port Huron Stadial age (about 13 000 years BP) of the Halton Till that underlies the silty clay, and suggests an age of between 12 500 – 13 000 years BP for glacial Lake Peel in the Brampton area that preceded the glacial Lake Iroquois phase in the Lake Ontario basin.